Navigating Digital Shifts in Arabic Language Education: A Contextual Inquiry in Indonesian Islamic Primary Schools - Tasniya Yusup; Muhammad Afthon Nuha (Learning, Media and Technology in Arabic Education, 2025)
Background of study: Arabic instruction in Indonesian Madrasah Ibtidaiyah often struggles with low student engagement and conventional methods. Aims: This research sets out to explore how digital technology is applied in Arabic language teaching at the elementary Islamic school level. It focuses on identifying the types of tools used, their influence on students’ learning experiences, and the obstacles faced during implementation. Methods: Using a qualitative descriptive approach, this study was carried out in a selected MI in Central Java. Data were collected through class observations, interviews with both teachers and students, and document reviews including lesson plans and instructional content. The analysis followed thematic coding to draw meaningful insights. Result: The findings reveal that digital platforms like Duolingo, Quizizz, and interactive videos positively affect students' interest and understanding, especially in vocabulary and pronunciation. Many students reported enjoying the learning process more when technology was involved. Nevertheless, issues such as limited access to devices, unstable internet connections, and varying digital competencies among teachers remained significant challenges. Conclusion: Integrating digital tools into Arabic language education at the MI level contributes positively to students' motivation and learning outcomes. However, its success relies heavily on continuous teacher training, improved infrastructure, and ensuring equal access to technology. A blended model that combines digital and traditional instruction appears to be a practical way forward.